Meningkatkan Efektivitas Pembelajaran Melalui Penggunakan Media Quizizz Pada Siswa SMA Negeri 4 Makassar - Thamrin Tahir; Muhammad Ilyas Thamrin Tahir; Amiruddin Tawe; Andi Tenri Ampa; Nurwahida Nurwahida (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
Effectiveness of using Quizizz media in collaborative learning and instilling it in learning styles and improving learning outcomes of class X-3 students of SMA Negeri 4 Makassar. The methods used are lectures, questions and answers or discussions, and training. The results obtained from using Quizizz media are able to improve students' understanding of economic material, encourage active involvement in discussion groups, and increase students' motivation and enthusiasm for learning. Quizizz has also been proven to be able to accommodate various learning styles and create an interactive and enjoyable learning atmosphere. Although there are obstacles such as technical problems and student adaptation to technology, in general the use of this media makes a positive contribution to the process and learning outcomes of students).